Stereotypical diel movement and dive pattern of male sperm whales in a submarine canyon revealed by land-based and bio-logging surveys - Amano, Masao; Aoki, Kagari; Kobayashi, Hayao; Minamikawa, Shingo; Sato, Katsufumi; Kubodera, Tsunemi (Frontiers in Marine Science, 2023)
Male sperm whales are under pressure to grow larger in order to increase their mating opportunities, which could lead them to more efficiently forage in high latitude feeding grounds. Movement patterns of male sperm whales in Nemuro Strait, Japan, were investigated horizontally and vertically using land-based observation and bio-logging methods to determine how they facilitate foraging in the narrow submarine canyon. Eleven tagged whales showed the distinct diel pattern for dive depth, as it was deeper at night than during the day. Five-year data of land-based observation and GPS data from six tagged whales revealed the tendency of whales to change the north-south direction of their horizontal movement every 4–6 h, and this movement direction was not related to the direction of the current. Their periodic heading change is thought to be a consequence of the whales making two round trips each day within the foraging area, one during the day to shallow layers and one during the night to deep layers. These tactics may help the whales to search for prey in this narrow submarine canyon efficiently. Most whales changed their direction of movement in a similar manner, which is probably due to the whales’ tendency to stay close enough to each other to obtain information about the prey environment using the echolocation clicks of other whales. The results emphasize the ability of male sperm whales to adapt their foraging tactics according to the prey environment of their habitat and intense pressure to grow faster may be the drive for this ability. The importance of social cohesion among foraging male sperm whales was also suggested.